HUBUNGAN ANTARA BIAYA MODAL EKUITAS DENGAN TINGKAT PENGUNGKAPAN TANGGUNG JAWAB SOSIAL DAN MODAL INTELEKTUAL PADA SEKTOR PERBANKAN DI INDONESIA - Sirait, Shanty Debora Yutriny; Siregar, Sylvia Veronica (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2012)
This study aims to test association between cost of equity capital and level of corporate social responsibility(CSR) and intellectual capital disclosure in banking sector in Indonesia. The samples in this study are listedbanks in Indonesia between 2007-2009 with total observations are 49 firm-years. The result of this studyshows that there is no significant association between subsequent years’s cost of equity capital and level ofCSR and intellectual capital disclosure in banking sector in Indonesia. Also there is no significant associationbetween change in level of CSR disclosure and the change of cost of equity capital in subsequent year. On theother side, significant and negative correlation is found between change in level of intellectual capitaldisclosure and the change of cost of equity capital in subsequent year.Keywords:cost of equity capital, CSR disclosure, intellectual capital, bank